2007
DOI: 10.1111/j.1399-0039.2007.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the selenoprotein S (SELS) gene −105G>A promoter polymorphism in inflammatory bowel disease and regulation of SELS gene expression in intestinal inflammation

Abstract: Recently, a -105G>A promoter polymorphism coding for selenoprotein S (SELS) has been shown to increase proinflammatory cytokine expression. We, therefore, analyzed SELS expression and potential phenotypic consequences of the -105G>A polymorphism in patients with inflammatory bowel disease (IBD). SELS mRNA was measured by quantitative polymerase chain reaction (PCR) in intestinal epithelial cells (IEC) after stimulation with proinflammatory cytokines and in human colonic biopsies of IBD patients as well as in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 40 publications
0
18
2
Order By: Relevance
“…In line with previous reports of significant associations of genetic variants in the STAT4 gene with the risk for autoimmune diseases such as SLE, rheumatoid arthritis [23], [27], [32] and psoriasis, [23], [36] our study could identify the STAT4 SNP rs7574865 also to be associated with the susceptibility to CD. However, this association to CD did not reach the extent of significance or clinical relevance shown for other CD susceptibility genes such as NOD2 / CARD15 and IL23R [5], [13], [14], [41][43]. For all other STAT4 gene variants investigated (rs11889341, rs7568275, rs8179673, rs10181656, rs7582694 and rs10174238), our analysis did not reveal any significant association with CD or UC susceptibility.…”
Section: Discussioncontrasting
confidence: 85%
“…In line with previous reports of significant associations of genetic variants in the STAT4 gene with the risk for autoimmune diseases such as SLE, rheumatoid arthritis [23], [27], [32] and psoriasis, [23], [36] our study could identify the STAT4 SNP rs7574865 also to be associated with the susceptibility to CD. However, this association to CD did not reach the extent of significance or clinical relevance shown for other CD susceptibility genes such as NOD2 / CARD15 and IL23R [5], [13], [14], [41][43]. For all other STAT4 gene variants investigated (rs11889341, rs7568275, rs8179673, rs10181656, rs7582694 and rs10174238), our analysis did not reveal any significant association with CD or UC susceptibility.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies have suggested that the SELS gene is dysregulated in diabetes, and the data presented here indicate that the C3705T and/or the A5227G polymorphisms may play a role in this context. However, the C-105T polymorphism, which showed the strongest association with circulating proinflammatory cytokines [10] but no direct association with inflammatory bowel disease [9] or rheumatoid arthritis [14], was not associated with metabolic risk factors analyzed in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…The observed difference in allele frequency of rs34713741 between patients with rectal cancer and controls (Tables 3, 4, 5) may reflect the close proximity (*100 bp) and likely linkage of rs28665122 and rs3471374 and changes in inflammatory events in the rectum, especially since altered inflammatory processes have been associated with increased CRC risk [17]. The previous failure to find any association between genotype for rs28665122 and susceptibility to inflammatory bowel disease [27] may reflect the small size of the population examined in that study. The present results suggest investigation of SELS association with gut inflammation using either mechanistic approaches or larger population groups would be worthwhile.…”
Section: Discussionmentioning
confidence: 96%